The role of humanistic leadership on good governance in sport organization: A literature review - Hartarto, Airlangga; Castyana, Billy; Mega Anggita, Gustiana; Ditya Candra, Adiska Rani; Setyawati, Heny (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Good organizational performance is also inseparable from good organizational management. However, not all Sports Organizations have a Good governance system, even though the governance system is a crucial component for managing a sports organization because it relates to policy issues and the direction of the performance of a sports organization. In addition, organizational performance is also inseparable from the intervention of organizational leaders because a leader has skills in influencing others to work together to achieve common goals. One of the successful leadership styles in business-based organizations is humanist leadership, but can humanist leadership styles contribute to realizing a sports organization that has Good Governance? A total of 20 articles in the last ten years on the topic of Good governance and humanist leadership were used as data and analyzed. Based on the results and discussion of the principles of Good Governance emphasized Transparency, Democracy, Check and Balance and Solidarity, and Humanist leadership, which has pillars such as communication, democracy, and transparency to its members. This study concludes that human leadership has a role in forming leaders who can improve the quality of good governance in sports organizations.